Bulgaria Policy Note : Financial Sector - World Bank (Washington, DC, 2014)
This report describes developments in the banking sector. The banking sector has remained stable throughout the ongoing financial crisis, although profitability is declining. Indicators suggest that banks are generally sound. It next describes the state of funding of bank operations, including wholesale bank funding. In response to financial stress, The Bulgarian National Bank's (BNB) actions have helped to ensure financial stability in the banking sector. In order to boost confidence, deposit insurance has increased. External funding dynamics are generally good. Foreign currency mismatches are substantial, and the corporate sector has high direct foreign currency exposure, mostly in euros. Short-term external debt (deposits and borrowings) of banks almost doubled within a year in 2008, and account for close to 80 percent of banks' external debt. Regarding recent trends in credit to the enterprise sector, going forward, demand for banking credit, and especially investment finance, will fall, in line with the economic downturn. In equity market developments, Bulgaria's stock market plunged, with adverse consequences for pension funds. Global deleveraging by foreign institutional investors led to a withdrawal of their holdings from the Sofia stock exchange, leading to a collapse of stock market prices. The report concludes with several policy recommendations.